The relationship of epicardial fat and atrial high-rate episodes in patients with permanent pacemaker - Hoşoğlu, Yusuf; Akkaya, Fatih; Kırış, Abdulkadir (The European Research Journal, 2023)
Objectives: Atrial high-rate episodes (AHRE) can occur in patients who have permanent pacemakers (PPM). AHRE is classified as subclinical atrial fibrillation (AF). Also, AHRE is related to clinical AF. Epicardial fat tissue (EFT) thickness is linked to AF. The purpose of this study was to examine the relation between AHRE and EFT thickness in PPM patients. Methods: Forty patients with dual-chamber PPM were enrolled. Transthoracic echocardiography was used to measure the thickness of the EFT. Patients were examined in 2 groups according to whether there was AHRE in the records: group 1 (AHRE) and group 2 (AHRE-free). A high atrial rate of more than 175 beats per minute for more than 5 minutes was defined as AHRE. The findings of the standard 2-dimensional echocardiography and the Doppler echocardiography were all recorded. A statistical relationship between EFT thickness and the development of AF was investigated. Results: Group 1 had ten patients, while Group 2 included thirty individuals. When the demographic features of the two groups were compared, they were similar. Both groups had similar 2-D echocardiographic and Doppler results. The difference in EFT thickness between groups 1 (2.0 ± 1.1 mm) and 2 (2.9 ± 1.8 mm) was not statistically significant (p = 0.138). Conclusions: In patients with PPM, AHRE may develop after implantation and may be detected asymptomatically in periodic follow-up. In this population, we did not observe a significant association between EFT thickness and the development of AF.